A New Digestion and Chemical Separation Technique for Rapid and Highly Reproducible Determination of Major Elements in Limestone Sample - VENUGOPAL, T.; GIRIDHARAN, L.; JAYAPRAKASH, M. (Asian Journal of Chemistry, 2010)
Analysis of varying grades of limestone samples were performed and a simple, rapid and sensitive method has been developed for all grades of limestone sample. The interference of silica and other metal oxides on the determination of limestone sample is studied. The method is found to be consistent and the results are very much comparable with the existing procedure. The results are in good agreement with the certified values of the reference standard samples. The novelty in the present study is fusion of the sample is avoided totally from high calcium content samples down to low grade limestone samples. Hence the method is very much suitable for analysis of sample spectrophotometrically.